COMPARISON OF CRIMINAL ACTIVITY BETWEEN ISRAELI VETERANS WITH AND WITHOUT PTSD. Issue 2 (2nd August 2013) - Sherman, Shany; Fostick, Leah; Zohar, Joseph; ,
<x xml:space="preserve">Abstract</x> Background The literature, based on US Vietnam veterans, suggests that posttraumatic stress disorder (PTSD) is associated with increased criminal activity, especially violence, alcohol, and drug abuse, although more recent studies, which tested data from the United States as well as the United Kingdom, suggest a more moderate effect for this relationship. The current study examines Israeli veterans, who differ socioeconomically and have lower rates of substance abuse than veterans in previous studies. Methods In this study, the social security numbers of 2, 235 male veterans with PTSD and 2, 235 matched control male veterans without a PTSD diagnosis were checked for criminal records in the Israeli Police criminal records database. Severity measures were also obtained for 273 veterans who are currently treated for PTSD by the Ministry of Defense. Results PTSD diagnosed veterans, as compared to controls, were slightly more likely to have criminal records (43%, n = 957/2235 versus 36%, n = 803/2235, Chi‐ square = 22.23, P < 0.001, OR = 1.33). This was due to a small difference in "Violence" and "Crimes against public order and legal authority." No difference was found in drugs or any other categories. In addition, criminal activity was not related to symptoms severity. More veterans with PTSD had their first criminal record after the traumatic event. Conclusions Contrary to previous findings, in this large national cohort, only slight association was found between PTSD and criminal activity. The unique sample of Israeli veterans might account for this difference and suggest that PTSD per se might not be linked to increased criminal activity, violence, or substance abuse.